A comparative analysis of intellectual capital disclosure practices between Malaysia and Indonesia / Zuraida Mohamad Noor, Amrizah Kamaluddin and Erlane K Ghani - Mohamad Noor, Zuraida; Kamaluddin, Amrizah; Ghani, Erlane K. (Universiti Teknologi MARA Cawangan Selangor, 2017)
This study examined the extent of intellectual capital (IC) disclosure practices between Malaysian and Indonesian agricultural companies. This study relied on content analysis on the annual reports of public listed agricultural companies in Malaysia and Indonesia. The results show that the extent of IC disclosure practices of the companies between the two countries are similar. However, the Malaysian companies disclose more information on human capital and are more quantitative in nature whilst the Indonesian companies disclose more information on relational capital and more qualitative. The results also show a significant positive relationship between the extent of IC capital disclosure and companies’ performance. The findings in this study contribute further understanding on the extent of IC capital disclosure in the agriculture industry. This study extends the understanding of the role of IC and its interaction in generating competitive edge from the perspective of a developing nation such as Malaysia and Indonesia.